Climate change projections of probable maximum precipitation over large areas through depth-area-duration analysis: A case study in Brazil - João Paulo Lyra Fialho Brêda; Walter Collischonn; Pedro Torres Miranda; Rodrigo Cauduro Dias de Paiva (Journal of Hydrology, 2026)

Crossing from shallow inshore to deep continental shelf habitats: Benthic-pelagic coupling and trophic position of the Lane snapper, Lutjanus synagris, in a tropical seascape - Rodrigo Ferreira Bastos; Alexandre Miranda Garcia; Thierry Frédou; François Le Loc'h; Gilvan Takeshi Yogui; Sergio Magalhães Rezende; Mauro Maida; Beatrice Padovani Ferreira (Marine Environmental Research, 2026)

Hyperdominance and Rarity in Amazonian Secondary Forests - Fernando Elias; Joice Ferreira; Erika Berenguer; Rodrigo Oliveira do Nascimento; Leonardo Miranda; Divino Vicente Silvério; Ima Célia Guimarães Vieira; Luiz E. O. Aragão; Gustavo Schwartz; Jos Barlow (Global Change Biology, 2026)
Recent studies have shown that a few tree species dominate abundance and carbon storage in undisturbed Amazonian forests. However, this pattern remains poorly understood in forests regrowing after deforestation. Understanding dominance patterns in secondary forests is important as it could improve insights into their functioning and guide management and restoration efforts. We used unweighted and novel plot‐weighted approaches to assess hyperdominance in abundance and carbon storage of trees and palms during secondary forest recovery, using data from 102 plots across four regions in the eastern Amazon, separated by an average distance of 600 km (range: 150–1000 km). Secondary forests show high levels of hyperdominance in all approaches, with just 15–25 species (3%–6%) accounting for over 50% of abundance and carbon storage. A small subset of species (~9%) were found across all regions and successional stages, highlighting their key role in ecosystem structure and function during forest regrowth. Annona exsucca , Cecropia palmata , Tapirira guianensis , and Inga alba formed a consistent core of hyperdominant species across stem size classes, metrics, and approaches, jointly accounting for roughly 16%–27% of total abundance and carbon storage. For larger stems ≥ 10 cm DBH, hyperdominant species exhibited lower wood density compared to non‐hyperdominant species across all successional stages, suggesting these specialist pioneers have distinct ecological strategies from the rest of the community. Our findings indicate that secondary forest functioning may be largely predicted by a relatively limited set of species, providing a framework for future research ranging from ecophysiology to remote sensing of canopy traits and restoration planning.

Gender identity and mate preferences: transgender individuals value emotional traits over facial attractiveness - Rodrigo de Menezes Gomes; Natália de Araújo Miranda Tasso; Fívia de Araújo Lopes; Felipe Nalon Castro (Evolution and Human Behavior, 2026)

Effect of a multivalent vaccination protocol on reproductive efficiency in Bos indicus beef females - Rodrigo de Morais; Fúlvio Picanço Florenzano; Adryele Araujo Borges Lima; Giovanna Meireles Borges; Sacha Manuelly da Silva Lobato; Daniel Rocha de Oliveira; Lorrayne Honorio de Paula; Weslen Fabricio Pires Teixeira; Moyses dos Santos Miranda; Rinaldo Batista Viana; Bruno Moura Monteiro (Animal Reproduction Science, 2026)

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

Reply to Figueroa‐Muñoz et al.'s comment on ‘multiple tools to investigate the origin of the exotic species Chinook salmon Oncorhynchus tshawytscha (Walbaum, 1792) (Salmonidae) in the world's largest chocked coastal lagoon’ - Yan Gonçalves Gowert; Valéria Marques Lemos; Fabiano Corrêa; Sabrina Vollrath; João Paes Vieira; Mario Vinicius Condini; Rodrigo Ferreira Bastos; Mylla Carla Cescon Freire; Ana Paula Cazerta Farro; Antonio Sergio Varela Junior; Cristiano Albuquerque; Maurício Hostim‐Silva; et al. (Journal of Fish Biology, 2026)

An expert elicitation approach for characterizing marine mammal and small-scale fisheries interactions: Insights from Chilean dolphin (Cephalorhynchus eutropia) bycatch - Stefan Gelcich; Rodrigo A. Estévez; Cayetano Espinosa-Miranda; Valentina Rebolledo-Zelada; Jorge Guerra; Sonja Heinrich; Carol Medrano; Carlos Olavarría; Cristopher Rodriguez-Jaramillo; Macarena Santos-Carvallo; Maritza Sepúlveda; María José Pérez-Álvarez (Ocean & Coastal Management, 2026)

Do the taxonomic and functional diversity of mobile macroinvertebrates in kelp forest reflect the habitat complexity? - Rigoberto Moreno-Mendoza; Luis Enrique Angeles-Gonzalez; Eduardo Hernández-Miranda; Rodrigo Riera; Christian Díaz (Regional Studies in Marine Science, 2026)

Validation of SMAP, SMOS, and ESA CCI SM soil moisture products in a seasonally dry tropical forest - Cloves Vilas Boas dos Santos; Josiclêda Domiciano Galvíncio; Rodrigo de Queiroga Miranda; Herica Fernanda de Sousa Carvalho; Alzira Gabrielle Soares Saraiva Souza; Inajá Francisco de Sousa; Magna Soelma Beserra de Moura (Journal of South American Earth Sciences, 2026)

Quality Assessment of Videos about Radiotherapy-Related Oral Mucositis on YouTube in Brazil - Yohana Cordeiro de Miranda Magno; Natália Santos Barcelos; Juliana Maria Braga Sclauser; Iara de Oliveira Nogueira; Rodrigo Richard da Silveira; Patrícia Carlos Caldeira (Journal of Cancer Education, 2025)

Bacillus and Paenibacillus Strains Enhance Nitrogen Metabolism and Increase Biomass Production of Nopalea Cochenillifera Grown in semi-arid Soil - Acacyara Batista de Sousa; Marcos Renan Lima Leite; Gonçalves Albino Dauala; Pâmalla Graziely Carvalho Morais; Stelamaris de Oliveira Paula Marinho; Gilnair Nunes Monteiro; Maria Helena Ferreira Duarte; Ruthanna Isabelle de Oliveira; Rodrigo Fonseca da Silva; Rhaiana Oliveira de Aviz; Rafael de Souza Miranda; Cácio Luiz Boechat; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Exploring the expression of MMP-2, MT1-MMP, and MMP-9 in the pectoral muscle of Ross chickens during E11, E15, and E19 of fetal development - Alisson Rodrigo de Oliveira; Maria Albertina de Miranda Soares; Jose Rosa Gomes (Histochemistry and Cell Biology, 2025)

Multiple tools to investigate the origin of the exotic species Chinook salmon Oncorhynchus tshawytscha ( W albaum, 1792) ( S almonidae) in the world's largest chocked coastal lagoon - Yan Gonçalves Gowert; Valéria Marques Lemos; Fabiano Corrêa; Sabrina Vollrath; João Paes Vieira; Mario Vinicius Condini; Rodrigo Ferreira Bastos; Mylla Carla Cescon Freire; Ana Paula Cazerta Farro; Antonio Sergio Varela Junior; Cristiano Albuquerque; Maurício Hostim‐Silva; et al. (Journal of Fish Biology, 2025)
Salmonid species have increasingly been established in South America for aquaculture and recreational fishing purposes. This study provides the first scientific record of the Chinook salmon ( Oncorhynchus tshawytscha ) in the Patos Lagoon (32°S), the world's largest choked coastal lagoon. The specimen was a female with 770 mm (total length), 3992.1 g, estimated age of 6 years and an advanced sexual maturation stage. Based on multiple tools (DNA barcoding, stable isotopes in eye lens, otolith growth layers and egg's histological analysis), we discussed potential entry routes for this species into the lagoon.

Sargassum-based biosorption for glyphosate removal: A green, efficient, and sustainable approach - J. Luis López-Miranda; Gustavo A. Molina; Alberto Elizalde-Mata; Rodrigo Esparza; Rodolfo Silva; Miriam Estevez (Journal of Environmental Chemical Engineering, 2025)

Low-current electrostimulation boosts Dunaliella salina growth on hypersaline produced water - Carine Souza da Silva; Gustavo Miranda Pires Santos; Gabriele Rodrigues Conceição; Ian da Silva Andrade; Alana Nogueira Silva; Rodrigo Miranda Pires Santos; Fabio Alexandre Chinalia (Algal Research, 2025)

Community structure of marine megafauna inhabiting the Gulf of Arauco: The role of natural and anthropogenic factors in its spatial-temporal dynamics - Eduardo Hernández-Miranda; Ninoska Figueroa; Santiago Miranda; Luís Montecinos; M. Cristina Krautz; Rodrigo Veas; Renato A. Quiñones (Marine Environmental Research, 2025)

Reproductive biology of Eremanthus incanus (Less.) Less., an endemic exploited Asteraceae from Brazil - Luiz Filipe Maravilha; João Paulo Raimundo Borges; Elisa Jorge de Morais; Evandro Luiz Mendonça Machado; Leonardo Ré Jorge; André Rodrigo Rech; Miranda Titon (Trees, 2025)

Probing the role of calcium carbonate on hydrothermal liquefaction of polyethylene in the presence of supercritical water - Kalsoom Jan; Daniel Lachos Perez; Akash Patil; Rodrigo Almeida Luciano; Débora M. Vaz de Miranda; Wan-Ting Chen (Chemical Engineering Journal, 2025)

Associations among production systems, identity aspects, microbiological results and physical-chemical traits as revealed by official analyses of Minas Artisanal Cheese (QMA, Queijo Minas Artesanal) - Amanda Rosário Alvim Santos; Caio Fialho de Freitas; Anderson Carlos Camargo; Rafael Bombachi; Liliane Denize Miranda Menezes; Antônio Fernandes de Carvalho; Sergio Santos de Azevedo; Cinzia Caggia; Rodrigo Alves Barros; Luís Augusto Nero (Food Control, 2025)

Effects of the insecticide thiodicarb on non-target organs and behavior of the stingless bee Partamona helleri (Hymenoptera: Meliponini) - Davy Soares Gomes; Franciane Rosa Miranda; João Victor de Oliveira Motta; Mateus Soares de Oliveira; Cliver Fernandes Farder-Gomes; Daniel Silva Sena Bastos; Rodrigo Cupertino Bernardes; Fernanda Pereira da Silva; Pollyana Leão Gonçalves; Hugo Bolsoni Zago; Cynthia Canêdo da Silva; Leandro Licursi de Oliveira; et al. (Pesticide Biochemistry and Physiology, 2025)

Taxonomic identity, but not evolutionary relatedness, determines the carbon stock and uptake of tropical forests trees - Alisson Borges Miranda Santos; Cléber Rodrigo de Souza; Fernanda Coelho de Souza; Natália de Aguiar-Campos; Vinicius Andrade Maia; Nathalle Cristine Alencar Fagundes; Aurélio de Jesus Rodrigues Pais; Gabriela Gomes Pires; Mariana Caroline Moreira Morelli; Jean Daniel Morel; Rubens Manoel dos Santos (Acta Oecologica, 2025)

Ascophyllum nodosum-derived biostimulant promotes physiological conditioning to increase soybean yield in a semiarid climate - Jeane Ferreira de Jesus; Amanda Soares Santos; Renato Oliveira de Sousa; Bruno Sousa Figueiredo da Fonseca; Wesley Santos Ferreira; Rodrigo Fonseca da Silva; Stelamaris de Oliveira Paula-Marinho; Priscila Alves Barroso; Milena Rodrigues Luz; Francisco de Alcântara Neto; José Hélio Costa; Rafael de Souza Miranda (Journal of Applied Phycology, 2024)

Reproductive phenology of the non-woody community in a seasonally dry tropical forest and woodland in northeastern Brazil - Sâmia Paula Santos Neves; Adelly Cardoso de Araujo Fagundes; Alexsandro Bezerra-Silva; Paulo Sérgio Neves dos Santos; David Rodrigo Rossatto; Lia d’Afonsêca Pedreira de Miranda; Ligia Silveira Funch (Journal of Arid Environments, 2024)

Subacute tributyltin exposure alters the development and morphology of mammary glands in association with CYP19A1 expression in female rats - Natalia P. Silva; Charles S. da Costa; Kayke L. Barbosa; Cidália de F. Januario; Leticia N. Gama-de-Souza; Cinthia Breves; Rodrigo S. Fortunato; Leandro Miranda-Alves; Miriane de Oliveira; Celia R. Nogueira; Jones B. Graceli (Reproductive Toxicology, 2024)

Exposure to the herbicide tebuthiuron affects behavior, enzymatic activity, morphology and physiology of the midgut of the stingless bee Partamona helleri - Cliver Fernandes Farder-Gomes; Franciane Rosa Miranda; Rodrigo Cupertino Bernardes; Daniel Silva Sena Bastos; Davy Soares Gomes; Fernanda Pereira da Silva; Pollyana Leão Gonçalves; Stella Arndt; André da Silva Xavier; Hugo Bolsoni Zago; José Eduardo Serrão; Gustavo Ferreira Martins; et al. (Environmental Toxicology and Pharmacology, 2024)

Water restriction alters seed bank traits and ecology in Atlantic Forest seasonal forests under climate change - Patrícia Borges Dias; Sustanis Horn Kunz; José Eduardo Macedo Pezzopane; Talita Miranda Teixeira Xavier; João Paulo Fernandes Zorzanelli; João Vitor Toledo; Lhoraynne Pereira Gomes; Rodrigo Gomes Gorsani (Global Change Biology, 2024)
The soil seed bank (SSB) is one of the key mechanisms that ensure the perpetuity of forests, but how will it behave in the scenarios projected for the future climate? Faced with this main question, still little explored in seasonal tropical forests, this study evaluated the germination, ecological attributes, and functional traits of the SSB in a seasonal forest in the Atlantic Forest. Forty‐eight composite samples of the SSB were collected from 12 plots, distributed across four treatments, each with 12 replicates. The samples were placed in two climate‐controlled greenhouses, establishing two environments of controlled climatic conditions, both with two levels of water, as follows: Cur: current scenario without water restriction; Cur_WR: current scenario with water restriction; RCP8.5: future scenario without water restriction; RCP8.5_WR: future scenario with water restriction. The germinants were identified, and their ecological attributes and functional traits were obtained. Leaf area and biomass production, differences in abundance, richness, and diversity were evaluated, along with analysis of variance to assess the interaction between water levels and scenarios. All ecological attributes and functional traits evaluated drastically decreased in the future projection with water restriction, with this restriction being the main component influencing this response. The increased temperature in the future scenario significantly raised water consumption compared to the current scenario. However, persistent water restrictions in the future could undermine the resilience of seasonal forests, hindering seed germination in the soil. Richness and abundance were also adversely affected by water scarcity in the future scenario, revealing a low tolerance to the projected prolonged drought. These changes found in the results could alter the overall structure of seasonal forests in the future, as well as result in the loss of the regeneration potential of the SSB due to decreased seed viability and increased seedling mortality.

Dynamics of experimental plantations of Tachigali vulgaris in response to fertilization and soil texture - Roberthi Alef Costa Teixeira; Michael Douglas Roque Lima; Arystides Resende Silva; Delman de Almeida Gonçalves; Leo Jakson da Silva Moreira; Rodrigo Otávio Veiga de Miranda; Ananias Francisco Dias Junior; Mario Tomazello-Filho; Alvaro Augusto Vieira Soares; Thiago de Paula Protásio (New Forests, 2024)

Exposure to low-concentration fipronil impairs survival, behavior, midgut morphology and physiology of Aedes aegypti larvae - Cliver Fernandes Farder-Gomes; Franciane Rosa Miranda; Kenner Morais Fernandes; Rodrigo Cupertino Bernardes; Daniel Silva Sena Bastos; Leandro Licursi de Oliveira; Gustavo Ferreira Martins; José Eduardo Serrão (Chemosphere, 2024)

Unraveling DEHP influence on hemoglobin S polymerization in sickle cell disease: Ex vivo, in vitro and in silico analysis - Rodrigo Abreu Camacho; Aghata Vitoria Machado; Fernanda de Oliveira Mendonça; Lyzes Rosa Teixeira-Alves; Camila Cristina Guimarães-Nobre; Evelyn Mendonça-Reis; Priscila Ferreira da Silva; Thyago R. Cardim-Pires; Leandro Miranda-Alves; Clemilson Berto-Junior (Toxicology in Vitro, 2024)

Terrestrial and Martian space weather: A complex systems approach - Abraham Chian; Rodrigo Miranda; Cesar Bertucci; Xóchitl Blanco-Cano; Joe Borovsky; Sergio Dasso; Ezequiel Echer; Adriane Franco; Kirolosse M. Girgis; J. Américo González-Esparza; Tohru Hada; Hiroshi Hasegawa; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Bikesharing and ordinary cyclists from Chile: Comparing trips, attitudes, and health-behaviours - Rodrigo Mora; Sebastián Miranda-Marquez; Ricardo Truffello; Kabir P. Sadarangani (Journal of Transport Geography, 2024)

Corrigendum to “Development of a knowledge-sharing parallel computing approach for calibrating distributed watershed hydrologic models” [Environ. Model. Software 164 (2023) 105708] - Marjan Asgari; Wanhong Yang; John Lindsay; Hui Shao; Yongbo Liu; Rodrigo De Queiroga Miranda; Maryam Mehri Dehnavi (Environmental Modelling & Software, 2024)

Phenotypic and genomic characterization of a non‐pathogenic Epilithonimonas ginsengisoli isolated from diseased farmed rainbow trout ( Oncorhynchus mykiss ) in Chile - Claudio D. Miranda; Rute Irgang; Christopher Concha; Rodrigo Rojas; Ruben Avendaño‐Herrera (Journal of Fish Diseases, 2024)
Flavobacterial infection associated with diseased fish is caused by multiple bacterial species within the family Flavobacteriaceae . In the present study, the Chilean isolate FP99, from the gills of a diseased, farmed rainbow trout ( Oncorhynchus mykiss ), was characterized using phenotypic and genomic analyses. Additionally assessed was pathogenic activity. Phylogenetic analysis based on 16S rRNA gene sequencing confirmed that isolate FP99 belonged to the genus Epilithonimonas , an average nucleotide identity value of 100% was detected with the Chilean isolate identified as Epilithonimonas sp. FP211‐J200. In silico genome analysis, mechanisms for toxins production, and superantigens, adhesion, or other genes associated with virulence were not detected. However, genes encoding proteins for antibiotic resistance were found, including the chrA gene and the nucleotide sequence that encodes for multiple antibiotic resistance MarC proteins. Furthermore, the bla ESP‐1 gene (87.85% aminoacidic sequence identity), encoding an extended‐spectrum subclass B3 metallo‐β‐lactamase and conferring carbapenem‐hydrolysing activity, and the tet (X) gene, which encodes a monooxygenase that catalyses the degradation of tetracycline‐class antimicrobials were carried by this isolate. Phenotyping analyses also supported assignment as E. ginsengisoli . Challenge trials against healthy rainbow trout resulted in no observed pathogenic effect. Our findings identify for the first time the species E. ginsengisoli as associated with fish farming, suggesting that this isolate may be a component of the microbiota of the freshwater system. Notwithstanding, poor environmental conditions and any stressors associated with aquaculture situations or lesions caused by other pathogenic bacteria, such as F. psychrophilum , could favour the entry of E. ginsengisoli into rainbow trout.

Towards implementing precision conservation practices in agricultural watersheds: A review of the use and prospects of spatial decision support systems and tools - Md. Bodrud-Doza; Wanhong Yang; Rodrigo de Queiroga Miranda; Alicia Martin; Ben DeVries; Evan D.G. Fraser (Science of The Total Environment, 2023)

Juvenile variable stress modulates, in female but not in male Wistar rats, ethanol intake in adulthood - Agustín Salguero; Agostina Barey; Rodrigo García Virgolini; Victoria Mujica; María Carolina Fabio; Roberto Sebastián Miranda-Morales; Leonardo Marengo; Rosana Camarini; Ricardo Marcos Pautassi (Neurotoxicology and Teratology, 2023)

Compositional and sensory attributes of Minas Frescal cheese obtained from Anglo Nubian, Moxoto, and Saanen goats in different lactation stages - Isis Miranda Carvalho Nicory; Thomaz Cyro Guimarães de Carvalho Rodrigues; Manuela Silva Libânio Tosto; Rodrigo Freitas Bittencourt; Lays Débora Silva Mariz; Marion Pereira da Costa; Gisele Rocha dos Santos; José Augusto Gomes Azevedo; Gleidson Giordano Pinto de Carvalho; Stefanie Alvarenga Santos (International Dairy Journal, 2023)

Nutritional attributes of goat milk obtained from Anglo Nubian, Moxoto, and Saanen breeds in different lactation phases - Isis Miranda Carvalho Nicory; Thomaz Cyro Guimarães de Carvalho Rodrigues; Manuela Silva Libânio Tosto; Rodrigo Freitas Bittencourt; Lays Débora Silva Mariz; José Augusto Gomes Azevedo; Gleidson Giordano Pinto de Carvalho; Stefanie Alvarenga Santos (International Dairy Journal, 2023)

Bj-PRO-10c, as an allosteric regulator of argininosuccinate synthase, is a potential therapy for neuroblastoma metastasis - Fernanda Coutinho; Lara MF. Guimarães; Rodrigo Seeger; Ana Paula J Santos; Talita Glaser; Denise Yamamoto; Lucas Lacerda; Vanessa Arnaud-Sampaio; Caio VT. Rossini; Izadora Rabelo; Nathália Miranda de Medeiros; Daniela Ramos Truzzi; et al. (Toxicon, 2023)

A firebreak placement model for optimizing biodiversity protection at landscape scale - Jaime Carrasco; Rodrigo Mahaluf; Fulgencio Lisón; Cristobal Pais; Alejandro Miranda; Felipe de la Barra; David Palacios; Andrés Weintraub (Journal of Environmental Management, 2023)

Subacute high-refined carbohydrate diet leads to abnormal reproductive control of the hypothalamic-pituitary axis in female rats - Jeanini Zimerman; Oscar M.S. Niño; Charles S. da Costa; Jordana F. Zanol; Milena Comério; Letícia N. da Gama de Souza; Leandro Miranda-Alves; Rosiane A. Miranda; Patrícia C. Lisboa; Tays A. Camilo; Rodrigo Rorato; Guilherme Andrade Alves; et al. (Reproductive Toxicology, 2023)

Glutamine supplementation accelerates functional recovery of EDL muscles after injury by modulating the expression of S100 calcium-binding proteins - Audrei R. Santos; Tatiana E. Koike; Alana M. Santana; Natalya C. Miranda; Rodrigo A. Dell Aquila; Thiago C. Silva; Marcelo S. Aoki; Elen H. Miyabara (Histochemistry and Cell Biology, 2023)

Deep Learning-Based Approaches for Oil Spill Detection: A Bibliometric Review of Research Trends and Challenges - Rodrigo N. Vasconcelos; André T. Cunha Lima; Carlos A. D. Lentini; José Garcia V. Miranda; Luís F. F. de Mendonça; José M. Lopes; Mariana M. M. Santana; Elaine C. B. Cambuí; Deorgia T. M. Souza; Diego P. Costa; Soltan G. Duverger; Washington S. Franca-Rocha (Journal of Marine Science and Engineering, 2023)
Oil spill detection and mapping using deep learning (OSDMDL) is crucial for assessing its impact on coastal and marine ecosystems. A novel approach was employed in this study to evaluate the scientific literature in this field through bibliometric analysis and literature review. The Scopus database was used to evaluate the relevant scientific literature in this field, followed by a bibliometric analysis to extract additional information, such as architecture type, country collaboration, and most cited papers. The findings highlight significant advancements in oil detection at sea, with a strong correlation between technological evolution in detection methods and improved remote sensing data acquisition. Multilayer perceptrons (MLP) emerged as the most prominent neural network architecture in 11 studies, followed by a convolutional neural network (CNN) in 5 studies. U-Net, DeepLabv3+, and fully convolutional network (FCN) were each used in three studies, demonstrating their relative significance too. The analysis provides insights into collaboration, interdisciplinarity, and research methodology and contributes to the development of more effective policies, strategies, and technologies for mitigating the environmental impact of oil spills in OSDMDL.

Acute Effects of Fluoxetine on Stress Responses and Feeding Motivation in Nile Tilapia - Julia P. G. A. Miranda; Ana Beatriz J. Isaac; Rebeca B. Silva; Leandro C. S. Toledo; Leonardo J. G. Barcellos; Helton Carlos Delicio; Rodrigo Egydio Barreto (Fishes, 2023)
The selective serotonin reuptake inhibitor fluoxetine is one of the most commonly administered psychotropic medications; however, it has been recognized as toxic to aquatic life. In this study, we showed that stress responses and feeding motivation in Nile tilapia were affected by acute exposure to fluoxetine. To reach that conclusion, we exposed Nile tilapia to 0, 1 or 10 µg/L (environmentally/biologically relevant doses) of fluoxetine over a 24 h period and then exposed them to a handling stressor. We found that the 10 µg/L dose enhanced cortisol response to stress but caused an earlier decrease in the ventilation boost induced by that stressor. An immediate ventilation boost after stressful stimuli indicates sympathetic activation. Thus, this suggests that fluoxetine decreased sympathetic nervous system activity but augmented hypothalamus–pituitary–interrenal axis activity in the fish. Both feeding latency and ingestion were similar among the tested conditions; however, a multiple logistic regression model revealed that in the presence of a stressor or fluoxetine, the Nile tilapia tended to ingest less food but there was a higher probability of this decrease to be associated with fluoxetine. We concluded that acute exposure to environmentally/biologically relevant fluoxetine concentrations over 24 h acted as a modifying factor for Nile tilapia stress physiology and tended to interfere with feeding motivation. An acute stress response is an emergency reaction that contributes to the recovery of homeostasis. In the presence of fluoxetine, modifications of acute stress responses and the tendency to reduce food intake, which restricts the ability to replace the energy spent on stress responses, could compromise the resumption of homeostasis and an animal’s adjustment to different environmental contexts, such as those associated with aquaculture, in which anthropogenic stressors inevitably occur.

Nitric oxide-loaded nano- and microparticle platforms serving as potential new antifungal therapeutics - Sichen Liu; Daniel Zamith-Miranda; Rodrigo Almeida-Paes; Leandro Buffoni Roque da Silva; Parimala Nacharaju; Joshua D. Nosanchuk (Fungal Biology, 2023)

Removal of VOCs using electro-Fenton assisted absorption process - Andrea N. Arias; Rocío Girón-Navarro; Ivonne Linares-Hernández; Verónica Martínez-Miranda; Elia Alejandra Teutli-Sequeira; Justo Lobato; Manuel A. Rodrigo (Journal of Environmental Chemical Engineering, 2023)

Development of a knowledge-sharing parallel computing approach for calibrating distributed watershed hydrologic models - Marjan Asgari; Wanhong Yang; John Lindsay; Hui Shao; Yongbo Liu; Rodrigo De Queiroga Miranda; Maryam Mehri Dehnavi (Environmental Modelling & Software, 2023)

Treatment of gaseous streams polluted with H2S: Comparison of electrolytic and electro-Fenton assisted absorption processes - Rocío Girón-Navarro; Andrea N. Arias; Ivonne Linares-Hernández; Verónica Martínez-Miranda; Elia Alejandra Teutli-Sequeira; Justo Lobato; Manuel A. Rodrigo (Chemosphere, 2023)

A review of 121 years of studies on the freshwater zooplankton of Brazil - Maria Stela Maioli Castilho-Noll; Gilmar Perbiche-Neves; Natan Guilherme dos Santos; Leilane Talita Fatoreto Schwind; Fernando Miranda Lansac-Tôha; Alan Cleber Santos da Silva; Bianca Ramos de Meira; Ciro Yoshio Joko; Cláudio Simões de Morais-Júnior; Edissa Emi Cortez Silva; Eneida Maria Eskinazi-Sant'Anna; Felipe Rafael Oliveira; et al. (Limnologica, 2023)

Novel clinical and immunological features associated with persistent post-acute sequelae of COVID-19 after six months of follow-up: a pilot study - Jiram Torres-Ruiz; Julieta Lomelín-Gascón; Jaquelin Lira Luna; Ana Sofia Vargas- Castro; Alfredo Pérez-Fragoso; Miroslava Nuñez-Aguirre; Beatriz Alcalá-Carmona; Abdiel Absalón-Aguilar; Jennifer T. Balderas-Miranda; José Luis Maravillas-Montero; Nancy R. Mejía-Domínguez; Carlos Núñez-Álvarez; et al. (Infectious Diseases, 2023)

Mapping the benefits and the exchange values of provisioning ecosystem services using GIS and local ecological knowledge in a high-Andean community - Santiago Madrigal-Martínez; Rodrigo J. Puga-Calderón; Janina Castromonte-Miranda; Vladimir A. Cáceres (Remote Sensing Applications: Society and Environment, 2023)

Growth-Promoting Effects of Thiamethoxam on Sugarcane Ripened With Sulfometuron-Methyl - Deise de Paula Silva; Lucas Moraes Jacomassi; Josiane Aparecida Viveiros Oliveira; Marcela Pacola Oliveira; Letusa Momesso; Gabriela Ferraz de Siqueira; Rodrigo Foltran; Rogério Peres Soratto; Leila Luci Dinardo-Miranda; Carlos Alexandre Costa Crusciol (Sugar Tech, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

High Abundance of Candidatus Arthromitus in Intestinal Microbiota of Seriolella violacea (Palm Ruff) under Reared Conditions - Jaime Romero; Natalia Catalán; Carolina Ramírez; Claudio Miranda; Marcia Oliva; Héctor Flores; María Romero; Rodrigo Rojas (Fishes, 2023)
Intestinal microbiota has been involved in several processes that benefit the host, such as digestion, nutrient metabolism, resistance to pathogens colonization and immune function. In this study, we investigated the diversity, composition and functional prediction of microbiota of reared Seriolella violacea (palm ruff) in the same cohort sampled at different times (7-, 8- and 9-month-old). Microbial community structure analyses, using 16S rRNA amplicon sequencing, revealed that the intestinal microbiota was dominated by the phyla Firmicutes, Proteobacteria, Fusobacteria and Tenericutes. At the genus level, Candidatus Arthromitus was the most abundant in all sampled timepoints, representing in average 78% of the bacterial community (ranging from 18 to 98%), corresponding to segmented filamentous bacteria, which are interesting because they have been associated with the maturation of immune responses in the gut and protecting the host from bacterial infections. The comparisons of the intestinal microbiota among the three groups showed differences in abundance of bacterial taxa and also in alpha diversity indexes (Shannon and Simpson), as well as beta diversity metrics (weighted and unweighted UniFrac). Potential functions of the intestinal microbiota of palm ruff were retrieved using Philipin and Tax4fun and these analyses revealed high levels of genes for sugar metabolism. To our knowledge, this study represents the first description of the intestinal microbiota of S. violacea.

Disentangling the role of soil bacterial diversity in phosphorus transformation in the maize rhizosphere - Yasmin Florentino Rodrigues; Fernando Dini Andreote; Antonio Marcos Miranda Silva; Armando Cavalcante Franco Dias; Rodrigo Gouvea Taketani; Simone Raposo Cotta (Applied Soil Ecology, 2023)

Seaweed restocking along the Chilean coast: History, present, and inspiring recommendations for sustainability - Carolina Oyarzo-Miranda; Ricardo Otaíza; Alexis Bellorín; J.M. Alonso Vega; Fadia Tala; Nelson A. Lagos; Fernanda X. Oyarzún; Rodrigo A. Estévez; Nicolás Latorre-Padilla; Ana María Mora Tapia; Luis Figueroa-Fábrega; Roddy Jara-Yáñez; et al. (Frontiers in Marine Science, 2023)
Several seaweed species are commercialized worldwide both due to high demand for food and feed and as a raw material for the extraction of phycocolloids such as agar, carrageenan, and alginates that are used broadly in the food, cosmetic, and pharmaceutical industries. Chile is the world’s leading marine seaweed biomass producer when it comes to the exploitation of natural kelp beds. This extraction pressure has persisted for decades and has resulted in a reduction in natural stocks along the benthic ecosystems of the Chilean coast. Over the last three decades, several strategies aimed at restoring seaweed stocks have been implemented (i.e., sexual and asexual reproduction, the use of spore-type propagules or fragments of thalli, and entire thallus transplants). Success rates have varied, but the biological feasibility of such strategies has been demonstrated for several species. However, technological improvements must be achieved to move from small-scale, pilot experiments to cost-effective restocking strategies that are easy to transfer to fisher communities and another end-user, scalable to marine field conditions, and socio-ecologically sustainable. Researchers in other geographic areas have explored similar pathways for developing kelp restocking strategies and have tackled the research gaps regarding its massification. This work summarizes the research activities carried out in recent decades in the search for sustainable strategies to restore algal stocks in Chile.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Functional characterization of the pUceS8.3 promoter and its potential use for ectopic gene overexpression - Rodrigo Rocha Fragoso; Fabricio Barbosa Monteiro Arraes; Isabela Tristan Lourenço-Tessutti; Vívian Jesus Miranda; Marcos Fernando Basso; André Vinicius Júlio Ferreira; Antônio Américo Barbosa Viana; Camila Barrozo Jesus Lins; Philippe Castro Lins; Stéfanie Menezes Moura; João Aguiar Nogueira Batista; Maria Cristina Mattar Silva; et al. (Planta, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Sensitive fluorescent chemosensor for Hg(II) in aqueous solution using 4’-dimethylaminochalcone - Marco Mellado; Nicole Roldán; Rodrigo Miranda; Luis F. Aguilar; Manuel A. Bravo; Waldo Quiroz (Journal of Fluorescence, 2022)

Oil spill detection based on texture analysis: how does feature importance matter in classification? - Rodrigo N. Vasconcelos; Carlos A. D. Lentini; André T. Cunha Lima; Luís F. F. Mendonça; Garcia V. Miranda; Elaine C. B. Cambuí; Diego Pereira Costa; Soltan Galano Duverger; Mainara B. Gouveia; José M. Lopes; Milton J. Porsani (International Journal of Remote Sensing, 2022)

Artificial light at night (ALAN) causes variable dose-responses in a sandy beach isopod - Diego Quintanilla-Ahumada; Pedro A. Quijón; Patricio H. Manríquez; José Pulgar; Manuel R. García-Huidobro; Cristian Miranda; Alfredo Molina; Rodrigo Zuloaga; Cristian Duarte (Environmental Science and Pollution Research, 2022)

Cognitive impairment in the HTLV-1 infection: a comparative study associated with functional performance - Jonas Jardim de Paula; Luiz Claúdio Romanelli; Renata Caetano Vieira de Faria; Anna Barbara Proietti; Leandro Fernandes Malloy-Diniz; Marco Aurélio Romano-Silva; Debora Marques de Miranda; Rodrigo Nicolato (Journal of NeuroVirology, 2021)

Leaf trait variability maintains similar leaf exchange rhythms in Hirtella glandulosa Spreng. (Chrysobalanaceae) populations growing on contrasting soil types in the Brazilian Atlantic Forest - Josevânia Carneiro de Oliveira; Marília Grazielly Mendes dos Santos; Sâmia Paula Santos Neves; Angela Pierre Vitória; Davi Rodrigo Rossatto; Lia d’Afonsêca Pedreira de Miranda; Ligia Silveira Funch (Brazilian Journal of Botany, 2021)

Climate and Land Cover Trends Affecting Freshwater Inputs to a Fjord in Northwestern Patagonia - Jorge León-Muñoz; Rodrigo Aguayo; Rafael Marcé; Núria Catalán; Stefan Woelfl; Jorge Nimptsch; Ivan Arismendi; Camila Contreras; Doris Soto; Alejandro Miranda (Frontiers in Marine Science, 2021)
Freshwater inputs strongly influence oceanographic conditions in coastal systems of northwestern Patagonia (41–45°S). Nevertheless, the influence of freshwater on these systems has weakened in recent decades due to a marked decrease in precipitation. Here we evaluate potential influences of climate and land cover trends on the Puelo River (640 m 3 s –1 ), the main source of freshwater input of the Reloncaví Fjord (41.5°S). Water quality was analyzed along the Puelo River basin (six sampling points) and at the discharge site in the Reloncaví Fjord (1, 8, and 25 m depth), through six field campaigns carried out under contrasting streamflow scenarios. We also used several indicators of hydrological alteration, and cross-wavelet transform and coherence analyses to evaluate the association between the Puelo River streamflow and precipitation (1950–2019). Lastly, using the WEAP hydrological model, land cover maps (2001–2016) and burned area reconstructions (1985–2019), we simulated future land cover impacts (2030) on the hydrological processes of the Puelo River. Total Nitrogen and total phosphorus, dissolved carbon, and dissolved iron concentrations measured in the river were 3–15 times lower than those in the fjord. Multivariate analyses showed that streamflow drives the carbon composition in the river. High streamflow conditions contribute with humic and colored materials, while low streamflow conditions corresponded to higher arrival of protein-like materials from the basin. The Puelo River streamflow showed significant trends in magnitude (lower streamflow in summer and autumn), duration (minimum annual streamflow), timing (more floods in spring), and frequency (fewer prolonged floods). The land cover change (LCC) analysis indicated that more than 90% of the basin area maintained its land cover, and that the main changes were attributed to recent large wildfires. Considering these land cover trends, the hydrological simulations project a slight increase in the Puelo River streamflow mainly due to a decrease in evapotranspiration. According to previous simulations, these projections present a direction opposite to the trends forced by climate change. The combined effect of reduction in freshwater input to fiords and potential decline in water quality highlights the need for more robust data and robust analysis of the influence of climate and LCC on this river-fjord complex of northwestern Patagonia.

Correction to: Combining machine learning and texture analysis to differentiate mediastinal lymph nodes in lung cancer patients - Allan F. F. Alves; Sérgio A. Souza; Raul L. Ruiz; Tarcísio A. Reis; Agláia M. G. Ximenes; Erica N. Hasimoto; Rodrigo P. S. Lima; José Ricardo A. Miranda; Diana R. Pina (Physical and Engineering Sciences in Medicine, 2021)

Combining machine learning and texture analysis to differentiate mediastinal lymph nodes in lung cancer patients - Allan F. F. Alves; Sérgio A. Souza; Raul L. Ruiz; Tarcísio A. Reis; Agláia M. G. Ximenes; Erica N. Hasimoto; Rodrigo P. S. Lima; José Ricardo A. Miranda; Diana R. Pina (Physical and Engineering Sciences in Medicine, 2021)

Assessing the viability of electro-absorption and photoelectro-absorption for the treatment of gaseous perchloroethylene - Martín Muñoz-Morales; Montse Castañeda-Juárez; Fernanda Lourdes Souza; Cristina Saez; Pablo Cañizares; Verónica Martínez-Miranda; Ivonne Linares-Hernández; Manuel Andrés Rodrigo (Environmental Science and Pollution Research, 2021)

Effects of curcumin supplementation on sport and physical exercise: a systematic review - Lara Gomes Suhett; Rodrigo de Miranda Monteiro Santos; Brenda Kelly Souza Silveira; Arieta Carla Gualandi Leal; Alice Divina Melo de Brito; Juliana Farias de Novaes; Ceres Mattos Della Lucia (Critical Reviews in Food Science and Nutrition, 2021)

Forest cover influences zooplanktonic communities in Amazonian streams - Ana Caroline Alcântara Missias Gomes; Leonardo Fernandes Gomes; Iris Roitman; Hasley Rodrigo Pereira; Antonio Felipe Couto Junior; Elizabeth Maria Mamede da Costa; Mariana Lessa Carneiro da Silva; Tamiel Khan Baiocchi Jacobson; Rômulo José da Costa Ribeiro; Reinaldo José de Miranda Filho; Mario Lucio de Avila; Ludgero Cardoso Galli Vieira (Aquatic Ecology, 2020)

Evaluation of a Dynamic Bioremediation System for the Removal of Metal Ions and Toxic Dyes Using Sargassum Spp. - J. Luis López-Miranda; Rodolfo Silva; Gustavo A. Molina; Rodrigo Esparza; A. R. Hernandez-Martinez; J. Hernández-Carteño; Miriam Estévez (Journal of Marine Science and Engineering, 2020)
This work presents the results obtained in the design and manufacture of a simple, economic and ecological filter based on Sargassum spp. (Sspp), consisting of the species S. natans and S. fluitans, for the elimination of organic and inorganic toxic substances. The main objective is to make use of Sspp, as the massive amounts of this alga arriving at the Mexican Caribbean coast have caused serious problems over recent years. The toxic substances treated were organic dyes (methyl blue, methyl orange and methyl red) and the metal ion, lead (II). To obtain optimal removal conditions, grinding of the Sspp used, its mass and humidity were evaluated. In the design of the filter the area, flow rate and the number of layers were evaluated. Removal rates of almost 100%, 65% and 25% were obtained for methylene blue, methyl red and methyl orange respectively, and in the case of lead (II), values up to 95% were obtained. After the tests, the Sspp was characterized, using Fourier Transform Infrared (FTIR) spectroscopy and scanning electron microscopy, showing the presence of the dyes and the ionic species. These results demonstrate the efficiency of the dynamic Sspp-based filtration system proposed, which can be industrially scaled for the treatment of water contaminated with these kinds of substances.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Chemical composition of essential oils from different parts of Protium heptaphyllum (Aubl.) Marchand and their in vitro antibacterial activity - Rodrigo S. C. Cabral; Cassia C. F. Alves; Hellen R. F. Batista; Wendel C. Sousa; Isabela S. Abrahão; Antônio E. M. Crotti; Mariana B. Santiago; Carlos H. G. Martins; Mayker L. D. Miranda (Natural Product Research, 2020)

Metals, arsenic, pesticides, and microcystins in tilapia (Oreochromis niloticus) from aquaculture parks in Brazil - Taciana Onesorge Miranda Lopes; Larissa Souza Passos; Luiza Valli Vieira; Ernani Pinto; Fabiane Dorr; Rodrigo Scherer; Nathacha de Andrade Salustriano; Maria Tereza Weitzel Dias Carneiro; Lais Frigini Postay; Levy Carvalho Gomes (Environmental Science and Pollution Research, 2020)

Animal performance in grass monoculture or silvopastures using tree legumes - Amanda Maria Gallindo dos Santos; José Carlos Batista Dubeux Junior; Mércia Virginia Ferreira dos Santos; Mario de Andrade Lira; Valéria Xavier de Oliveira Apolinário; Suellen Brandão de Miranda Costa; Diego de Lima Coêlho; Thaíse Virgínia Freire Ramos Peixôto; Erick Rodrigo da Silva Santos (Agroforestry Systems, 2020)

Temporal shifts on tree species niches: how do they affect species dynamics and community diversity? - Vinícius Andrade Maia; Natalia de Aguiar-Campos; Cléber Rodrigo de Souza; Nathalle Cristine Alencar Fagundes; Alisson Borges Miranda Santos; Aurélio de Jesus Rodrigues Pais; Jean Daniel Morel; Camila Laís Farrapo; Rubens Manoel dos Santos (Plant Ecology, 2020)

ATLANTIC MAMMALS : a data set of assemblages of medium‐ and large‐sized mammals of the Atlantic Forest of South America - Yuri Souza; Fernando Gonçalves; Laís Lautenschlager; Paula Akkawi; Calebe Mendes; Mariana M. Carvalho; Ricardo S. Bovendorp; Hugo Fernandes‐Ferreira; Clarissa Rosa; Maurício Eduardo Graipel; Nivaldo Peroni; Jorge José Cherem; et al. (Ecology, 2019)
Biodiversity inventories contain important information about species richness, community structure, and composition, and are the first step in developing any conservation and mitigation strategies. The Atlantic Forest of South America is home to around 334 species of small‐, medium‐, and large‐sized mammals, and is currently restricted to less than 12% of its original cover. Here, we present the ATLANTIC MAMMALS , an open data set on information on medium‐ and large‐sized mammal assemblages in the Atlantic Forest of Brazil, Paraguay, and Argentina. A total of 129 studies were compiled, including published and in press peer‐reviewed papers, book chapters, theses and unpublished data. We mapped 244 assemblages, eight orders, 63 genera, and 94 species (24 of which are classified as threatened by the IUCN Red List) distributed in 128 protected and 116 unprotected areas. Species richness of the mammalian assemblages varied from 1 to 39 species (mean 15). The most recorded species in the entire biome was Dasypus novemcinctus , followed by Cerdocyon thous and Procyon cancrivorous . These data can be useful in support of macroecological studies and conservation planning strategies. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Cattle herd shearing can help to control Rhipicephalus microplus ticks - Cecília José Veríssimo; Rodrigo Giglioti; Selma Marques D’Agostino; Luciandra Macedo de Toledo; Luciana Morita Katiki; Keila Maria Roncato Duarte; Isabel Kinney Ferreira de Miranda Santos (Experimental and Applied Acarology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Spatial and temporal distribution of metals in PM2.5 during 2013: assessment of wind patterns to the impacts of geogenic and anthropogenic sources - Rodrigo Garza-Galindo; Ofelia Morton-Bermea; Elizabeth Hernández-Álvarez; Sara L. Ordoñez-Godínez; Omar Amador-Muñoz; Laura E. Beramendi-Orosco; Armando Retama; Javier Miranda; Irma Rosas-Pérez (Environmental Monitoring and Assessment, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

The cluster [Re6Se8I6]3− penetrates biological membranes: drug-like properties for CNS tumor treatment and diagnosis - Lisbell D. Estrada; Elizabeth Duran; Matias Cisterna; Cesar Echeverria; Zhiping Zheng; Vincenzo Borgna; Nicolas Arancibia-Miranda; Rodrigo Ramírez-Tagle (BioMetals, 2018)

HTLV-1 proviral load in cerebrospinal fluid may not be a good marker to differentiate asymptomatic carriers with high proviral load in blood from HAM/TSP patients - Marina Lobato Martins; Anna Bárbara de Freitas Carneiro-Proietti; Rodrigo Nicolato; Débora Marques de Miranda; Luiz Cláudio Ferreira Romanelli (Journal of NeuroVirology, 2018)

Influence of porosity of low-density polyethylene media on the maturation process of biofilters used in recirculating aquaculture systems - Túlio Pacheco Boaventura; Kleber Campos Miranda-Filho; Rodrigo Lambert Oréfice; Ronald Kennedy Luz (Aquaculture International, 2018)

Atmospheric PM2.5 Mercury in the Metropolitan Area of Mexico City - Ofelia Morton-Bermea; Rodrigo Garza-Galindo; Elizabeth Hernández-Álvarez; Sara L. Ordoñez-Godínez; Omar Amador-Muñoz; Laura Beramendi-Orosco; Javier Miranda; Irma Rosas-Pérez (Bulletin of Environmental Contamination and Toxicology, 2018)

Recognition of the importance of geogenic sources in the content of metals in PM2.5 collected in the Mexico City Metropolitan Area - Ofelia Morton-Bermea; Rodrigo Garza-Galindo; Elizabeth Hernández-Álvarez; Omar Amador-Muñoz; Maria Elena Garcia-Arreola; Sara L. Ordoñez-Godínez; Laura Beramendi-Orosco; Graciela L. Santos-Medina; Javier Miranda; Irma Rosas-Pérez (Environmental Monitoring and Assessment, 2018)

The roles of rainfall, soil properties, and species traits in flowering phenology along a savanna-seasonally dry tropical forest gradient - Sâmia Paula Santos Neves; Lia d´Afonsêca Pedreira de Miranda; Davi Rodrigo Rossatto; Ligia Silveira Funch (Brazilian Journal of Botany, 2017)

Leaf phenology and morphofunctional variation in Myrcia amazonica DC. (Myrtaceae) in gallery forest and “campo rupestre” vegetation in the Chapada Diamantina, Brazil - Aline Cristina da Silva Moraes; Angela Pierre Vitória; Davi Rodrigo Rossatto; Lia d’Afonsêca Pedreira de Miranda; Ligia Silveira Funch (Brazilian Journal of Botany, 2017)

Tissue reaction of deproteinized bovine bone matrix grafting in ectopic site: histological study on sheep - João Ricardo Almeida Grossi; Rodrigo Bonacin; Viviane Rozeira Crivelaro; Allan Fernando Giovanini; João César Zielak; Tatiana Miranda Deliberador (Cell and Tissue Banking, 2016)

The invasive species Ulex europaeus (Fabaceae) shows high dynamism in a fragmented landscape of south-central Chile - Adison Altamirano; Jenny Paola Cely; Andrés Etter; Alejandro Miranda; Andres Fuentes-Ramirez; Patricio Acevedo; Christian Salas; Rodrigo Vargas (Environmental Monitoring and Assessment, 2016)

Gene Expression Profile of NF-κB, Nrf2, Glycolytic, and p53 Pathways During the SH-SY5Y Neuronal Differentiation Mediated by Retinoic Acid - Matheus Augusto de Bittencourt Pasquali; Vitor Miranda de Ramos; Ricardo D′Oliveira Albanus; Alice Kunzler; Luis Henrinque Trentin de Souza; Rodrigo Juliani Siqueira Dalmolin; Daniel Pens Gelain; Leila Ribeiro; Luigi Carro; José Cláudio Fonseca Moreira (Molecular Neurobiology, 2016)

Microbiological functioning, diversity, and structure of bacterial communities in ultramafic soils from a tropical savanna - Marco Pessoa-Filho; Cristine Chaves Barreto; Fábio Bueno dos Reis Junior; Rodrigo Rocha Fragoso; Flávio Silva Costa; Ieda de Carvalho Mendes; Leide Rovênia Miranda de Andrade (Antonie van Leeuwenhoek, 2015)

Body shape and burial behavior of the sand crab Emerita analoga (Stimpson 1857) in a reflective to intermediate morphodynamic range of sandy beaches - Rodrigo Veas; Eduardo Hernández-Miranda; Renato A. Quiñones (Marine Biology, 2014)

The effect of sex and genotype on growth performance, feed efficiency, and carcass traits of local sheep group Pantaneiro and Texel or Santa Inês crossbred finished on feedlot - Fernando Miranda de Vargas Junior; Charles Ferreira Martins; Guilherme dos Santos Pinto; Marcos Barbosa Ferreira; Hélio de Almeida Ricardo; André Gustavo Leão; Alexandre Rodrigo Mendes Fernandes; Alfredo Teixeira (Tropical Animal Health and Production, 2014)

Epibenthic macrofaunal community response after a mega-earthquake and tsunami in a shallow bay off central-south Chile - Eduardo Hernández-Miranda; José Cisterna; Ernesto Díaz-Cabrera; Rodrigo Veas; Renato A. Quiñones (Marine Biology, 2014)

Marine intrusion and freshwater discharge as opposite forces driving fish guilds distribution along coastal plain streams - Rodrigo Ferreira Bastos; Lauro Júlio Calliari; Alexandre Miranda Garcia (Hydrobiologia, 2014)

Feeding ecology and prey preferences of a piscivorous fish in the Lagoa do Peixe National Park, a Biosphere Reserve in Southern Brazil - Fabiano Corrêa; Marlucy Coelho Claudino; Rodrigo Ferreira Bastos; Sônia Huckembeck; Alexandre Miranda Garcia (Environmental Biology of Fishes, 2012)

Antipredator Behavior of Brown Howlers Attacked by Black Hawk-eagle in Southern Brazil - João M. D. Miranda; Itiberê P. Bernardi; Rodrigo F. Moro-Rios; Fernando C. Passos (International Journal of Primatology, 2006)

Land‐use change effects on local energy, water, and carbon balances in an Amazonian agricultural field - Ricardo K. Sakai; David R. Fitzjarrald; Osvaldo L.L. Moraes; Ralf M. Staebler; Otávio C. Acevedo; Matthew J. Czikowsky; Rodrigo da Silva; Eleazar Brait; Valdelirio Miranda (Global Change Biology, 2004)
To study how changing agricultural practices in the eastern Amazon affect carbon, heat and water exchanges, a 20 m tower was installed in a field in August 2000. Measurements include turbulent fluxes (momentum, heat, water vapor, and CO 2 ) using the eddy covariance (EC) approach, soil heat flux, wind, and scalar profiles ( T , q , and CO 2 ), soil moisture content, terrestrial, total solar radiation, and photosynthetically active radiation (PAR, 400–700 nm). At the beginning of the measurements, in September 2000, the field was a pasture. On November 2001, the pasture was burned, plowed, and planted in upland (nonirrigated) rice. Calm nights were the norm in this site. Anomalously low values of net ecosystem exchange (NEE) were found using the EC method, even when the common criterion u * −1 was used to identify and exclude poor performance nights. We observed more plausible values of NEE using criterion u * −1 , indicating that the criterion must be revised downward for flow over surfaces smoother than forests. However, even using the lower threshold, u * was lower than this limit for 82% of nights, and this led to nocturnal respiration underestimates. We compensate for this difficulty by estimating the respiration rate using the nocturnal boundary layer budget method. Land‐use change from pasture to rice cultivation strongly affected both diurnal rates of turbulent exchange but also the pattern of seasonal variation. Seasonal wet and dry season differences in vegetation state were clearly detected in the albedo and PAR‐albedo. These reflectivity changes were accompanied by modified net radiative flux, turbulent heat flux and evaporation rates. The highest evaporation rate was observed during the rice crop, when the field had total evaporation approximately half the precipitation input, less than that of the surrounding forest. Effects of the land‐cover changes were also detected in the carbon budget. For the pasture, the maximum CO 2 uptake occurred in May, appreciably delayed from the start of the rainy season. After the field was plowed and the soil was exposed and there was efflux of CO 2 to the atmosphere day and night for an extended period. Highest values of carbon uptake occurred during the rice plantation. Although the upland rice took up carbon at double the rate of the pasture that it replaced, the field was left fallow for much of the year, during the dry season.